Assistive technologies for the blind: key competences for health promotion under the Galway Consensus - Carvalho, Luciana Vieira de; Melo, Gleicia Martins de; Aquino, Priscila de Souza; Castro, Régia Christina Moura Barbosa; Cardoso, Maria Vera Lúcia Moreira Leitão; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2017)
Objective: to identify the key competence domains defined in the Galway Consensus Conference Statement present in assistive technologies to promote the health of blind adults. Methods: integrative review carried out in the Latin American and Caribbean Health Sciences Literature, SCOPUS, Cumulative Index to Nursing and Allied Health Literature, and Medical Publications portal. After application of inclusion criteria, the sample consisted of 10 articles. Eight competencies for health promotion were analyzed: Catalyzing change, Leadership, Assessment of needs, Planning, Implementation, Advocacy, and Partnerships. Results: the competences Catalyzing change and Partnerships prevailed, present in all articles. No study approached the Leadership and Advocacy. Conclusion: the competences Catalyzing change, Assessment of needs, Planning, Implementation, Evaluation and Partnerships were observed in technologies for promoting the health of blind adults.